Effect of Polycyclic Aromatic Hydrocarbons Exposure on Cognitive Development in 5 Years Old Children - Blazkova, Barbora; Pastorkova, Anna; Solansky, Ivo; Veleminsky, Milos; Veleminsky, Milos; Urbancova, Katerina; Vondraskova, Veronika; Hajslova, Jana; Pulkrabova, Jana; Sram, Radim J (Brain sciences, 2020)
Objectives: To analyze the impact of polycyclic aromatic hydrocarbons (PAHs) in ambient air at the time of delivery and five years of age on cognitive development in five year old children. Materials and Methods: Two cohorts of children born in the years 2013 and 2014 from Karvina (Northern Moravia, n = 70) and Ceske Budejovice (Southern Bohemia, n = 99) were studied at the age of five years for their cognitive development related to the exposure to PAHs, determined in the ambient air as the concentration of benzo[a]pyrene (B[a]P) and OH-PAH (hydroxy-PAH) metabolites in urine of the newborns at the time of delivery. As psychological tests, the Bender Visual Motor Gestalt Test (BG test) and the Raven Colored Progressive Matrices (RCPM test) were used. Results: Concentrations of B[a]P in the third trimester of mother's pregnancies were 6.1 ± 4.53 ng/m3 in Karvina, and 1.19 ± 1.28 ng/m3 (p < 0.001) in Ceske Budejovice. Neither the outcome of the RCPM test nor the BG test differed between children in Karvina vs. Ceske Budejovice, or boys vs. girls. Cognitive development in five year old children was affected by the higher exposure to PM2.5 during the third trimester in girls in Karvina. Conclusions: We did not observe any significant effect of prenatal PAH exposure on psychological cognitive tests in five year old children.
Keywords: polycyclic aromatic hydrocarbons; Raven Colored Progressive Matrices; Bender Visual Motor Gestalt Test; psychological tests; OH–PAH metabolites in urine; cognitive development